O Trânsito Religioso e a Recomposição das Formas Religiosas na Igreja Evangélica Assembleia de Deus, Ministério São Bernardo do Campo - Costa, Emerson Roberto da (2011)
In its current configuration, the Brazilian religious field has an extremely diverse formatting of identity from that observed in previous decades. From this consideration emerges a significant problematic how to understand these changes? Why a scenario before highly resistant to change, nowadays it is opened to the modern winds allowing the recovery of its religious forms? Now, the construction of new identities and the reordering of religious standards can be understood from the phenomenon of religious transit, considering it is possible to identify in the movement of individuals a dynamic that establish changes in both institutional and litur-gical character of the groups, as well as in living of practice of the faithful, encouraging original and provisional symbolic systems. Given the multiplicity of supply, the subjects have a constant mobility in a continuous process of redefinition, forming ephemeral mosaics that are distinguished in multiple colors, shapes, space, demands, motivations, behaviors, interests, habitus, traditions, symbols, rules, strategies, tastes and combinations. From the postulates of the Religious Sciences, this research proposes to examine this event as the universe of observation with the Evangelical Assembly of God Ministry Sao Bernardo do Campo. It aims to demonstrate, through the interpretation of the data set ob-tained in field research correlated with the theoretical foundations, the rebuilding of religious forms and new institutional identities developed by individuals from mobility; to establish a connection between the elements and indicators of the research and the phenomenon characterized to identify what are the motivations of gender, class, generational and ethnic group for the transit of men and women who move in many different alternatives to this religious group and, given this framework, to understand how the religious institution absorbs the flow of people.